PATIENT PROFILE NAVIGATED BY NURSES: TIME INTERVAL FOR START OF TREATMENT - Juliana Pompeu Pecoraro; Patricia dos Santos Claro Fuly (Cogitare Enfermagem)
OBJECTIVE: Describe and analyze the sociodemographic and clinical profile and the interval between diagnosis and cancer treatment according to the gender of patients navigated by nurses in high complexity.